Impact of ASUMA Intervention on HIV Risk Behaviors among Puerto Rican Adolescents - Fernandez-Santos, Diana M. (Int J Environ Res Public Health, 2015)
The purpose of this manuscript is to assess and compare HIV risk behaviors among early adolescents after a three-year pilot study. A total of 135 public and private junior high schools students completed the intervention protocol. A self-administered questionnaire was given at baseline and at the end of the third year (fourth measure). Descriptive and inferential analyses were performed using SPSS 20.0. About 60% of the students were 14 years old at the fourth measure. The proportion of students that did not report at least one HIV risk behavior at baseline and those that reported any risk behavior at the fourth measure was lower in the intervention group (45.0%) than in the control group (54.5%). The proportion of students that reported at least one HIV risk behavior at baseline and those that did not report any HIV risk behavior at the fourth measure was higher in the intervention group than in the control group (33.3% vs. 8.3%). The proportion of students engaging in HIV risk behaviors was higher in the control group than in the intervention group at the fourth measure, suggesting that A Supportive Model for HIV Risk Reduction in Early Adolescence (ASUMA) intervention might be a promising initiative to reduce adolescents’ engagement in HIV risk behaviors.